2020
DOI: 10.2174/1874372202014010016
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Carbon-Dioxide Laser Plus Topical Clotrimazole versus Oral Itraconazole plus Topical Clotrimazole for Onychomycosis: A Randomized, Controlled Trial

Abstract: Background: Treating onychomycosis is problematic for a variety of reasons. The very nature of the hard, protective nail plate itself makes it difficult for topical drugs to reach the fungal pathogens beneath it. Oral therapy is more effective than topical therapy, but it is expensive, requires monitoring for toxicity, and can result in multiple drug interactions. Objectives: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The results of this and other studies 9 , 10 suggest that laser therapy is not effective in treating onychomycosis. Until now laser treatments have not kept their promises in onychomycosis treatment, and well‐designed successful clinical trials are still missing.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The results of this and other studies 9 , 10 suggest that laser therapy is not effective in treating onychomycosis. Until now laser treatments have not kept their promises in onychomycosis treatment, and well‐designed successful clinical trials are still missing.…”
Section: Discussionmentioning
confidence: 50%
“…Some of the hypotheses already published are the heat fungicidal action over fungi, keratin proteins denaturation, the possible laser influence on cellular oxidative reactions, and changes in host immune modulation. [11][12][13][14] The results of this and other studies 9,10 suggest that laser therapy is not effective in treating onychomycosis. Until now laser treatments have not kept their promises in onychomycosis treatment, and well-designed successful clinical trials are still missing.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, other studies show that toenail onychomycosis is more common than fingernail onychomycosis 35. The low incidence of toenail onychomycosis in this study may be attributed to the use of open footwear and lesser concern for the appearance of the feet and toenails [35] .…”
Section: Sitementioning
confidence: 56%
“…When compared with antifungal agent groups, few patients reported slight pain in CO 2 laser groups, and transient, minimal effects did not affect patient compliance in the continuance of treatment protocols. However, some patients in the itraconazole‐treated group from the study by Chau 11 reported gastrointestinal effects (3), abdominal pain (1) headache (2), and asymptomatic self‐limited liver transaminases elevation (2).…”
Section: Resultsmentioning
confidence: 99%